Characteristics, Management, and Outcomes of Patients With Osteosarcoma: An Analysis of Outcomes From the National Cancer Database. (February 2022) - Ottesen, Taylor D.; Shultz, Blake N.; Munger, Alana M.; Sibindi, Cosmas; Yurter, Alp; Varthi, Arya G.; Grauer, Jonathan N.
Abstract : Introduction: Previous studies about osteosarcoma patient characteristics, management, and outcomes have limited patient numbers, combine varied tumor types, and/or are older studies. Methods: Patients with osteosarcoma from the 2004 to 2015 National Cancer Database data sets were separated into axial, appendicular, and other. Demographic and treatment data as well as 1-, 5-, and 10-year survival were determined for each group. A multivariate Cox analysis of patient variables with the likelihood of death was performed, and the Kaplan Meier survival curves were generated. Results: Four thousand four hundred thirty patients with osteosarcoma (3, 435 appendicular, 810 axial, and 185 other) showed survival at 1-year, 5-year, and 10-year and was highest among the appendicular cohort (91.17%, 64.43%, and 58.58%, respectively). No change in survival was seen over the periods studied. The likelihood of death was greater with increasing age category, distant metastases, and treatment with radiation alone but less with appendicular primary site, treatment with surgery alone, or surgery plus chemotherapy. Discussion: Despite advances in tumor management, surgical excision remains the best predictor of survival for osteosarcomas. No difference was observed in patient survival from 2004 to 2015 and, as would be expected, distant metastases were a poor prognostic sign, as was increasing age, male sex, and axial location.